Linkage Between Human Resource Management and Firm Performance - Singh, Avinash (Journal of Commerce and Trade, 2016)
The impact of human resource management (HRM) policies and practices on firm performance is an important topic in the field of human resource management. In theoretical literature and the emerging conventional wisdom among human resource professionals there is a growing consensus that organizational human resource policies can, if properly configured, provide a direct and economically significant contribution to firm performance. A critical reading of the academic literature shows that the relationship between human resource management and firm effectiveness is a phenomenon with major implications on organizational performance. Objective of this research is to determine key determinants of formal human resource planning that contributes towards performance in the Private Banking Sector. The data collected from 25 offices including head offices from Allahabad District of U.P. Results from the factor analysis on HRP measures selection, training, and incentives and the organizational performance measures which arejob satisfaction, efficiency, employee motivation and technology constitutes significant and a positive relationship with other. As modern HR practices are implemented in telecom sector and companies would spend more on Human Resources, it would lead towards High performance achievement. This paper comprehensively studies the links between human resource management practice and firm performance and highlights the points how HRM practices can improve the organizational performance.